Tubercular mastitis - A case report with uncommon presentation - Aggarwal, Prerna; Sharma, Sushmita; Singh, Pradeep; Kaur, Maninder; Manhas, Ashwini; Bala, Manju (Asian Journal of Medical Sciences, 2014)
Tuberculosis of the breast is significant due to its rare occurrence and mistaken identity with breast cancer and pyogenic breast abscess. It typically affects young lactating multiparous women and can present either as an abscess or as a unilateral, painless breast mass. A case of 22 year unmarried female presented with discharge breast and a small abscess. Radiological and cytological methods remained nonspecific and tubercular mastitis was diagnosed on Zeihl Neelsen staining and culture for Mycobacteria. A multifaceted approach is needed to reach the correct diagnosis. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10143 Asian Journal of Medical Sciences Vol.6(1) 2015 119-121